A Study of the Mastery of Complex Sentences of Pre-Service English Teachers - Subekti, Adaninggar Septi (Universitas Ahmad Dahlan, 2017)
This study reported a research conducted to find out the mastery of complex sentences of students of Writing 5 of an English Education Program in Indonesia. The participants of the research were 24 pre-service English teachers in a Writing 5 class at an English Education program in Indonesia. It used document analysis as the main method of data collection. The study obtained some important findings. First, complex sentences containing multiple clause structures became the most frequently written of all, and among the four types of complex sentences, ones containing multiple clause structures became the most frequently written of all complex sentences. Secondly, studentsâ mastery of complex sentences containing noun clauses, adjective clauses, and adverb clauses was good. Their mastery of complex sentence containing multiple clause structures, however, was surprisingly very low despite that the students had obtained relatively good results on the three above-mentioned basic types of complex sentence.Â Keywords: Mastery, complex sentences, noun clauses, adjective clauses, adverb clauses, multiple clause structures